Comparing the prognosis of those with initial shockable and non-shockable rhythms with increasing durations of CPR: Informing minimum durations of resuscitation. (April 2016) - Grunau, Brian; Reynolds, Joshua C.; Scheuermeyer, Frank X.; Stenstrom, Robert; Pennington, Sarah; Cheung, Chris; Li, Jennifer; Habibi, Mona; Ramanathan, Krishnan; Barbic, David; Christenson, Jim
Abstract: Aim: There is little data to inform the appropriate duration of resuscitation attempts for out-of-hospital cardiac arrest (OHCA). We assessed the relationship of elapsed duration since commencement of resuscitation and outcomes, highlighting differences between initial shockable and non-shockable rhythms. Methods: We examined consecutive adult non-traumatic EMS-treated OHCA in a single health region. We plotted the time-dependent accrual of patients with ROSC, as well as dynamic estimates of outcomes as a function of duration from commencement of professional resuscitation, and compared subgroups dichotomized by initial rhythm. Logistic regression tested the association between time-to-ROSC and outcomes. Results: Of 1627 adult EMS-treated cases of OHCA, 1617 patients were included; 14% survivors and 10% with favorable neurological outcomes. Time-to-ROSC (per minute increase) was independently associated with survival in those with initial shockable (aOR 0.95, 95% CI 0.92–0.97) and non-shockable (aOR 0.83; 95% CI 0.78–0.88) rhythms. Similar associations were seen with favorable neurologic outcome. The elapsed duration at which the probability of survival fell below 1% was 48 and 15 min in the shockable and non-shockable groups, respectively. Median time-to-termination of resuscitation was 36 and 26 min in the shockable and non-shockable groups, respectively. Conclusion: The subgroup of initial shockable rhythms showed a less pronounced association of time-to-ROSC with outcomes, and demonstrated higher resilience for neurologically intact survival after prolonged periods of resuscitation. This data can guide minimum durations of resuscitation, however should not be considered as evidence for termination of resuscitation as survival in this cohort may have been improved with longer resuscitation attempts.